Oriano de Almeida (1921 - 2004): um estudo analítico-interpretativo e uma edição de quatro Prelúdios Potiguares - Paiva, Igara Cynara Cabral de (2011)
This research is an analytical and interpretative study about four pieces from Prelúdios Potiguares series written by pianist Oriano de Almeida (1921 - 2004) and an edition proposal of such pieces. The research was divided into three main methodological steps: data collection on Oriano de Almeida and Prelúdios Potiguares and bibliography related to the issues raised during the research; formal, phraseological and melodic analysis of the chosen preludes; and the elaboration of an edition of the preludes analyzed. These steps clarified the formal and phraseological structures adopted by the composer, as well as scales, modes and rhythms used; it also pointed discrepancies and errors observed in the comparative analysis of the sources taken as reference for this study and finally, the edition of preludes No Caminho do Sertão, Sequilhos e Alfinins, O Alvissareiro da Torre da Matriz and Comprai Juá Jucá. It was concluded that the compositional style of Oriano de Almeida presented in Prelúdios Potiguares is essentially improvisational and that the use of rhythms such as baião and maxixe, as well as the northeastern modes, gave the works the sound typically associated with the universe of northeastern popular music. This research intended to bring up problems related to editions of Brazilian music, as well as encourage other researchers to contribute on improving these materials. We sought to collaborate with the publication of piano works by Oriano de Almeida, in awakening interest to Brazilian music, and to incite the performance of piano works written by composers known only locally or regionally.